Telecommunications universal service guidelines approved by ECTEL Council July 2008 [and] adopted by the National Telecommunications Regulatory Commission July 2009 (ECTEL, 2009)
Provides guidelines for the efficient implementation of Universal Service in telecommunications in the Member States of the Eastern Caribbean Telecommunications Authority (ECTEL). Outlines the broad policy framework for Universal Service implementation and sets out the required standards and procedures for proper management of the Universal Service Funds in Grenada.
Keywords: TELECOMMUNICATIONS